Young Latin American Volcanologist network: achievements and future perspectives two years after its launch - Forte, Pablo (2018)
The development of volcanology in Latin America is marked by a common regional scenario, with countries sharing borders, socio-cultural characteristics and facing similar scientific challenges. This scenario illustrates the need to create and promote regional networks. In this abstract we present the Jóvenes Volcanólogos Latinoamericanos (JVLA) network, a specific strategy that gathers early career volcanologists from Latin America and aims to strengthen volcanology in the region by encouraging the active participation of new generations. A benchmark in the construction of this network was the CoV9 conference (2016, Chile), where the 1st meeting of Young Latin American Volcanologists took place. As a response to the needs identified during that meeting, JVLA, together with the Asociación Latinoamericana de Volcanología (ALVO), developed an internship program in volcano observatories for highly motivated Latin American volcanology students. In addition to offering the young volcanologists scientific training and experience working in a volcano observatory, this program aims to promote the interaction and cooperation between universities and observatories. With the financial support of IAVCEI, a pilot test of the program will be carried out during the 2018 austral winter at the Observatorio Volcanológico de los Andes del Sur (OVDAS), in Chile. Among other actions, JVLA has been using social media and specialized newsletters (i.e., Gaceta ALVO and IAVCEI Newsletter) to distribute relevant information and to share personal experiences. Recently, on 25 April 2018, JVLA organized the 2nd Meeting of Young Latin American Volcanologist in Arequipa, Peru. In the future, the JVLA network expects to continue promoting new activities and initiatives (e.g., meetings, summer schools, internship programs) that strengthen the bonds between the new generations of Latin American volcanologists and to enhance the development of volcanology at a regional, and consequently, world-wide scale.